2006
DOI: 10.1002/ecja.20296
|View full text |Cite
|
Sign up to set email alerts
|

Radiation properties of modified fractal microstrip antennas

Abstract: SUMMARYThis paper describes the method of configuration and the radiation properties of a new type of multi-band planar antenna with a radiating element made of a microstrip antenna (MSA) with a slit-loaded modified Sierpinski Gasket fractal antenna. In order to verify the multiband characteristics of this antenna, triangular MSA elements loaded with slits of a modified Sierpinski Gasket structure are fabricated. According to the experiment, the present test antenna exhibits excellent multiband characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Tada et al reported a modified Sierpinski gasket microstrip antenna (SG-MSA) using an Lprobe as a feeding system. Excellent multiband performances could be achieved over the three operating frequencies without fail [3]. Rhombic microstrip antenna with multiple inverted V-shaped slots fed by the L-probe was reported as a useful model for multiband operation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tada et al reported a modified Sierpinski gasket microstrip antenna (SG-MSA) using an Lprobe as a feeding system. Excellent multiband performances could be achieved over the three operating frequencies without fail [3]. Rhombic microstrip antenna with multiple inverted V-shaped slots fed by the L-probe was reported as a useful model for multiband operation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, along with multiband and wideband applications of wireless communication devices, research on fractal antennas with multiband characteristics has been carried out extensively [1][2][3][4][5][6][7][8][9][10][11][12]. However, this type of antenna has mainly been used for the radiating elements of a monopole antenna with a three-dimensional configuration for multiband operation [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Sierpinski gasket microstrip antenna (SG-MSA) fed by the embedded L-probe with a doublelayer dielectric substrate was reported by Tada et al as a multiband planar antenna [5]. Three operating frequencies with excellent radiation properties were achieved.…”
Section: Introductionmentioning
confidence: 99%